Differences between cardiac implantable electronic device envelopes evaluated in an animal model. (11th October 2020) - Ip, James E.; Xu, Linna; Lerman, Bruce B.
Abstract: Introduction: Cardiac implantable electronic device (CIED) pocket related problems such as infection, hematoma, and device erosion cause significant morbidity and the clinical consequences are substantial. Bioabsorbable materials have been developed to assist in the prevention of these complications but there has not been any direct comparison of these adjunctive devices to reduce these complications. We sought to directly compare the TYRX absorbable antibacterial and CanGaroo extracellular matrix (ECM) envelopes in an animal model susceptible to these specific CIED‐related complications (i.e., skin erosion and infection). Methods and Results: Sixteen mice undergoing implantation with biopotential transmitters were divided into three groups (no envelope = 4, TYRX = 5, and CanGaroo = 7) and monitored for device‐related complications. Following 12 weeks of implantation, gross and histological analysis of the remaining capsules was performed. Three animals in the CanGaroo group (43%) had device erosion compared to none in the TYRX group. The remaining capsules excised at 12 weeks were qualitatively thicker following CanGaroo compared to TYRX and no envelope and histological evaluation demonstrated increased connective tissue with CanGaroo. Conclusion: CanGaroo ECM envelopes did not reduce the incidence of device erosion and were associated with qualitatively thicker capsules and connective tissue staining at 12 weeks compared to no envelope or TYRX. Further studies regarding the use of these envelopes to prevent device erosion and their subsequent impact on capsule formation are warranted.